Suppressors of Cytokine Signaling in Sickness and in Health of Pancreatic β-Cells - Ye, Cheng; Driver, John P. (Frontiers in Immunology, 2016)
Suppressors of cytokine signaling (SOCS) are a family of eight proteins that negatively regulate JAK-STAT signaling in cells that utilize this pathway to respond to extracellular stimuli. SOCS are best known for attenuating cytokine signaling in the immune system. However, they are also expressed in many other cell types, including pancreatic β-cells where there is considerable interest in harnessing SOCS molecules to prevent cytokine-mediated apoptosis during diabetes and allogeneic transplantation. Apart from their potential as therapeutic targets, SOCS molecules play a central role for regulating important functions in β-cells, including growth, glucose sensing and insulin secretion. This review will discuss SOCS proteins as central regulators for diverse cellular processes important for normal β-cell function as well as their protective anti-apoptotic effects during β-cell stress.